Cover Feature: Double‐Shelled Hollow SiO2@N‐C Nanofiber Boosts the Lithium Storage Performance of [PMo12O40]3− (Chem. Eur. J. 53/2021). Issue 53 (21st August 2021) - Hu, Hanbin; Yang, Yixin; Jiang, Xiao; Wang, Jiaxin; Cao, Dongwei; He, Lei; Chen, Wei; Song, Yu‐Fei
Abstract : Excellent lithium storage is achieved by the double‐shelled hollow PMo12 ‐SiO2 @N‐C anode material. The outermost N‐C shell can improve the electronic conductivity and promote the dispersion of PMo12 clusters. The SiO2 inner shell can efficiently avoid the loss of active components. The hollow structure can buffer the volume expansion and accelerate Li + diffusion during lithiation/delithiation process. More information can be found in the Full Paper by L. He, W. Chen, Y.‐F. Song et al. (DOI: 10.1002/chem.202101638 ).